A novel micropump design: Investigation of the voltage effect on the net flow rate - Hamid Asadı Dereshgı; Mustafa Zahid Yıldız (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
A low cost piezoelectric micropump was designed andfabricated to supply fluid flow rate in micro-sizes and for use in medicalpurposes. It was designed as disposable in order to prevent contamination andinfection. The micropump was fabricated with the Objet260 Connex3multi-material 3D printer, which was very precise and sensitive. Thepiezoelectric was selected as an actuator to drive the diaphragm of thismicropump. The piezoelectric diameter was 14mm, the thickness was 200 µm andthe operating voltages were between 5V-55V. According to the experimentsresults, the air in the chamber caused reduction of the net flow rate of themicropump. Therefore, we eliminated the air inside the chamber with ethanolbefore the experiments. In the proposed micropump, we obtained the highest netflow rate and the maximum displacement of diaphragm at 55V that were 40.3ml/minand 2.64µm respectively.